Types of birds in oil palm plantation areas west pasaman district - Hafizha Ihsan; Ramadhan Sumarmin (Bioscience, 2021)
Birds that are members of vertebrate animals (vertebrates) that have feathers and wings, this taxonomic animal belongs to the Aves class. Birds have important roles in ecosystems, among others, as pollinators, seed dispersers, and pest control. Biodiversity in areas determined by habitat and level of human activity, as well as various species of birds in homogeneous forest areas such as oil palm. This research was conducted in January 2019 until May 2019, using the Visual Encounter Survey (VES) and Point Count method which was conducted in 3 observation sessions (morning, afternoon, evening). The research data will be presented in tabular form and analyzed descriptively. The results obtained are 3 species of birds in the area of oil palm plantations, namely Cekakak Shrub (Halcyon smyrnensis), Tekukur (Streptopelia chinensis), and Large Lathe (Centropus sinensis). Burung adalah anggota vertebrata yang memiliki bulu dan sayap, termasuk dalam Kelas Aves. Burung memiliki peran penting dalam ekosistem sebagai penyerbuk, penyebar benih, dan pengendalian hama. Keanekaragaman hayati di kawasan tersebut ditentukan oleh habitat dan tingkat aktivitas manusia, serta berbagai jenis burung di kawasan hutan homogen seperti kelapa sawit. Penelitian ini dilaksanakan pada bulan Januari sampai Mei 2019, dengan menggunakan metode Visual Encounter Survey (VES) dan Point Count dalam 3 waktu pengamatan (pagi, siang, dan sore). Total hanya 3 jenis burung yang ditemukan di daerah penelitian, yaitu Semak Cekakak (Halcyon smyrnensis), Tekukur (Streptopelia chinensis), dan Bubut Besar (Centropus sinensis).